Editorial: type D personality and its relationship with depression and disease activity in inflammatory bowel disease. Issue 1 (9th June 2021) - Knowles, Simon R.; Mikocka‐Walus, Antonina
LINKED CONTENT: This article is linked to Jordi et al papers. To view these articles, visit https://doi.org/10.1111/apt.16365 and https://doi.org/10.1111/apt.16398